Terapi Kognitif Perilaku dan Kecemasan Menghadapi Prosedur Medis Pada Anak Penderita Leukemia - Hinggar Ganari Mawandha; Endang Ekowarni (Universitas Islam Indonesia, 2009)
Anxiety facing medical procedures always happenes in children with chronic disease. The aim of this research is to examine the effect of cognitive behavior therapy to reduce anxiety facing medical procedures in children with leukemia. Beginning from children's concept about their experince in hospital, cognitive behavior therapy has been used to reduce anxiety by changing cognition, emotion, and behavior. This research uses the single subject design with three participant, age seven to 11 years old. To measure anxiety, an adapted anxiety scale and the checklist of positive behavior had used. Cognitive behavior therapy administered individually, applied in five sessions. Quantitative analysis by visual inspection was conducted to show the anxiety score fluctuations. Qualitative analysis was done by analyzing the diaries, observation results, and interview results. The research show that cognitive behavior therapy can reduce the level of anxiety facing medical prosedures in children with leukemia.Keywords: cognitive behavior therapy, anxiety, medical procedures, leukemia